Exploring Soundscape Perception in the Historical Catur Gatra Tunggal Area, Kotagede, through the Soundwalk - Kusumawardani, Neni; Marcillia, Syam Rachma (Jurnal Planologi, 2025)
Kotagede Yogyakarta is a historical area left behind by the Islamic Mataram Kingdom.  Now that district developing into a residential area. This area has a legacy of Javanese spatial structure and spatial pattern known as the concept of "Catur Gatra Tunggal”. However, the condition of this area has experienced physical and functional degradation, which affects the character of the space, including the quality of the sound environment (soundscape). This study aims to identify the current soundscape conditions in the Catur Gatra Tunggal Kotagede area through the soundwalk method to explore the types of sounds that exist in the current location and how humans perceive these sounds. Data collection was carried out on weekday dan weekend in three time spans. This study contributes to soundscape research by applying perception-based methods to culturally significant urban heritage areas, revealing spatial-temporal variations in auditory experience. The main conclusion of this study shows that there are differences in the dominance of soundscape formation at each location and the perception of these sounds. The activities at the location also determine the type of sound heard and how participants feel it according to their respective locations.Keywords: Acoustic environment, Heritage urban space, Kotagede, Perceived affective quality, Soundscape, Soundwalk methode